2018
DOI: 10.35808/ersj/1060
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Competence, Training, and Compensation to Employment Performance

Abstract: Working staff at PT Asuransi Jiwa Bringin Jiwa Sejahtera (BRI life) achieved satisfactory and less than satisfactory assessment based on Performance Management Unit (SMK), thus it needs to be improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 3 publications
2
5
0
2
Order By: Relevance
“…Therefore, to succeed in the execution of job duties, competence as an individual trait is necessary. In a Katidjan et al (2018); Dina Rande (2016) concluded that competence has a positive and essential impact on success are previous research findings that support this relationship. Thus, statement 5 may be rendered as follows: H5: The improvement of skills has a positive and vital impact on performance.…”
Section: Literature Reviewmentioning
confidence: 86%
“…Therefore, to succeed in the execution of job duties, competence as an individual trait is necessary. In a Katidjan et al (2018); Dina Rande (2016) concluded that competence has a positive and essential impact on success are previous research findings that support this relationship. Thus, statement 5 may be rendered as follows: H5: The improvement of skills has a positive and vital impact on performance.…”
Section: Literature Reviewmentioning
confidence: 86%
“…Tingkat keberhasil perusahaan akan sangat tergantung pada kualitas manusia yang ada dalam perusahaan. Diantara salah satu upaya yang dapat dilakukan yaitu melalui pengembangan secara terarah dan terencana, sehingga perusahaan dapat untuk bersaing (Katidjan, 2018). Menurut (Riyadi, 2020) bahwa penempatan karyawan pada posisi yang sesuai merupakan salah satu cara dalam menghasilkan Sdm yang baik dan berkualitas sesuai dengan kompetensinya.…”
Section: Pendahuluanunclassified
“…Menurut Katidjan, (2018) konsep manajemen talenta didasarkan pada keinginan manusia yang ingin dipelihara di perusahaan karena kelebihannya. Keterampilan sumber daya manusia yang didukung oleh pengalaman kerja yang matang adalah kemampuan sumber daya manusia.…”
Section: Pendahuluanunclassified
“…The effectual employment of training and development sessions is sightseen as a psychological pact among employers as well as employees; the performance of human resources can be affected positively and negatively based on equal availability of training and development programs to all the hired employees (Kuvaas, 2007). Katidjan, Pawirosumarto, & Yuliani (2018) emphasized that training and development is the key to improving the staff performance by inculcating both hard as well as soft skills, relevant expertise, and social competence in terms of doing collaborative work with others through contributing voluntarily to the fulfillment of an organizational goal. As understanding and cooperating with colleagues is related to performing extra duties which are the main facet of contextual performance (Turnipseed & Rassuli, 2005).…”
Section: Training and Development Adaptive Performance And Contextual Performance In The Presence Of Nepotism And Favoritismmentioning
confidence: 99%